Trace element composition of modern planktic foraminifera from an oxygen minimum zone: Potential proxies for an enigmatic environment - Davis, Catherine V.; Doherty, Shannon; Fehrenbacher, Jennifer; Wishner, Karen (Frontiers in Marine Science, 2023)
Oxygen limited marine environments, such as oxygen minimum zones, are of profound importance for global nutrient cycling and vertical habitat availability. While it is understood that the extent and intensity of oxygen minimum zones are responsive to climate, the limited suite of viable proxies for low oxygen pelagic environments continues to pose a real barrier for paleoclimate interpretations. Here we investigate the proxy potential of an array of trace element (Mg, Mn, Zn, and Sr) to Ca ratios from the shells of Globorotaloides hexagonus, a planktic foraminifer endemic to tropical through temperate oxygen minimum zones. A species-specific relationship between Mg/Ca and temperature is proposed for quantitative reconstruction of oxygen minimum zone paleotemperatures. Both Mn/Ca and Zn/Ca ratios vary with oxygen concentration and could be useful for reconstructing G. hexagonus habitat where the primary signal can be dfrom diagenetic overprinting. Finally, a robust correlation between Sr/Ca ratios and dissolved oxygen demonstrates a role for Sr as an indicator of oxygen minimum zone intensity, potentially via foraminiferal growth rate. The analysis of these relatively conventional trace element ratios in the shells of an oxygen minimum zone species has tremendous potential to facilitate multiproxy reconstructions from this enigmatic environment.